A Convenient Method to Prepare Novel Alkali Metal Potassium Doped Carbon Nitride Photocatalyst with Tunable Band Structure - Zhao1, Y.F.; Zhang2, J.; Wang2, Y.J. (Asian Journal of Chemistry, 2014)
A novel alkali metal ion K+ doped carbon nitride photocatalyst with a tunable band structure was prepared using dicyandiamide monomer and potassium hydrate as precursor. X-ray diffraction, UV-visible, FT-IR and XPS were used to characterize the prepared catalysts. The valence band and conduction band potentials were obviously altered by changing the potassium concentration. Besides, the addition of potassium inhibited the crystal growth of graphitic carbon nitride and increased the separation rate of photogenerated electrons and holes. The visible-light-driven Rhodamine-B photodegradation performance was significantly improved after K+ doping. The possible doping site and influence mechanism of potassium concentration on photocatalytic performance was proposed.